2019
DOI: 10.5935/0004-2749.20190018
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated collagen cross-linking in the management of advanced Acanthamoeba keratitis

Abstract: To report our initial experience in the treatment of Acanthamoeba keratitis with accelerated corneal collagen cross-linking. Methods: Retrospective chart review of patients diagnosed with Acanthamoeba keratitis with progressive corneal melting who were treated with accelerated collagen cross-linking. Results: A total of 6 eyes (5 patients) were reviewed. All the patients received adjuvant therapy with moxifloxacin and chlorhexidine. In 4 cases, the ulcer healed with a mean interval to epithelialization of 108.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Some clinical studies reported interesting outcomes of epi-off CXL on acanthamoeba keratitis. [144,145] However, several in vitro studies have shown that riboflavin mediated CXL did not confer any positive effect on acanthamoeba cyst or trophozoites [146,147] whereas Rose Bengal mediated CXL did. [146].…”
Section: Photoactivated Chromophore CXL For Infectious Keratitis (Pac...mentioning
confidence: 98%
“…Some clinical studies reported interesting outcomes of epi-off CXL on acanthamoeba keratitis. [144,145] However, several in vitro studies have shown that riboflavin mediated CXL did not confer any positive effect on acanthamoeba cyst or trophozoites [146,147] whereas Rose Bengal mediated CXL did. [146].…”
Section: Photoactivated Chromophore CXL For Infectious Keratitis (Pac...mentioning
confidence: 98%
“…High fluence PACK-CXL treatment may also target disease burden in AK, leading to pain relief, re-epithelization, and elimination of Acanthamoeba [118]. In another study, PACK-CXL halted corneal melting in the setting of AK [120]. While further investigation is needed, PACK-CXL may be a useful adjunctive therapy in recalcitrant AK.…”
Section: Photodynamic Therapy/cross-linkingmentioning
confidence: 99%
“…The addition of autophagy inhibitors to multipurpose contact lens solution (MPS) reduced the adhesion rate of Acanthamoeba trophozoites to silicone hydrogel contact lenses compared with MPS with PHMB 46. There are case reports of adjunctive corneal crosslinking successfully improve or stabilize advanced AK 47–51…”
Section: Treatment Of Refractory Akmentioning
confidence: 99%
“…46 There are case reports of adjunctive corneal crosslinking successfully improve or stabilize advanced AK. [47][48][49][50][51] ' Clinical Example A 64-year-old physician was referred to the Massachusetts Eye and Ear emergency department for cornea consultation for 3 weeks of left eye pain and corneal ulceration. His past ocular history was significant for contact lens use in left eye only, for monovision.…”
Section: Treatment Of Refractory Akmentioning
confidence: 99%